2012
DOI: 10.1159/000337942
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Phosphate Binding and Loading Alter Kidney Angiotensin-Converting Enzyme mRNA and Protein Content in 5/6 Nephrectomized Rats

Abstract: Background: Vitamin D receptor activation with paricalcitol can modulate the transcription of renin-angiotensin system components in the surgical 5/6 nephrectomy rat model (5/6 NX) of chronic renal insufficiency. We tested the hypothesis whether dietary modification of phosphate influences kidney renin-angiotensin system gene expression at the mRNA level in 5/6 NX rats. Methods: Fifteen weeks after surgery, rats were given control diet (0.3% calcium, 0.5% phosphate), phosphate-lowering diet (3% calcium as carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 53 publications
(48 reference statements)
3
47
0
Order By: Relevance
“…18,184,185 Extracellular phosphate concentrations have also been associated with increased production of profibrotic mediators and may have a direct stimulatory effect on RAAS. [186][187][188] There is some evidence supporting the role of phosphorus in the pathogenesis of feline CKD. Early studies evaluating phosphate restricted diets showed that cats on restricted diets had reduced evidence of renal histopathological lesions (calcification, fibrosis and inflammatory cell infiltration) compared to cats on a high phosphorus diet.…”
Section: Hyperphosphatemiamentioning
confidence: 99%
“…18,184,185 Extracellular phosphate concentrations have also been associated with increased production of profibrotic mediators and may have a direct stimulatory effect on RAAS. [186][187][188] There is some evidence supporting the role of phosphorus in the pathogenesis of feline CKD. Early studies evaluating phosphate restricted diets showed that cats on restricted diets had reduced evidence of renal histopathological lesions (calcification, fibrosis and inflammatory cell infiltration) compared to cats on a high phosphorus diet.…”
Section: Hyperphosphatemiamentioning
confidence: 99%
“…Clinical and experimental data indicate that elevated plasma phosphate (Pi) may contribute to progression of chronic kidney disease (CKD) [1,2,3,4,5] by a not fully elucidated mechanism. In spite of that, the effect of high Pi levels per se on kidney cells may play a role, since it has been shown that addition of higher Pi concentrations to the culture medium of kidney fibroblasts elicits increased extracellular matrix (ECM) production [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, functional and structural changes in resistance arteries have been described in both clinical [3] and experimental chronic renal insufficiency (CRI) [4]. Phosphate retention, hypocalcemia, increased fibroblast growth factor 23, and reduced vitamin D levels lead to the development of secondary hyperparathyroidism already at stages 2 and 3 of CRI [5,6], and these factors also influence the remodeling of the vascular wall [7]. In order to manage CRI-induced hyperphosphatemia and hyperparathyroidism, oral phosphate binders are frequently needed [8].…”
Section: Introductionmentioning
confidence: 99%
“…A key target for the pharmacological inhibition of the renin-angiotensin system is angiotensin-converting enzyme (ACE), which converts angiotensin I (Ang I) to Ang II and degrades kinins [13]. We recently found that dietary phosphate loading was associated with increased kidney ACE expression and tissue damage in the 5/6 nephrectomy (NX) rat model of CRI [5]. In contrast, phosphate binding with 3.0% calcium carbonate reduced kidney ACE and tissue damage [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation